La Contextualisation Des Banques de Ressources: Barrières et Clés - Aude Dufresne; Alain Senteni; Griff Richard (The Canadian Network for Innovation in Education (CNIE), 2002)
When developing learning resource banks for telearning, it is important to recognize known barriers to the re-use of learning objects and some possible solutions. First, in order that the resources be reused, they must have been created in a modular fashion, separating the resources from their intended context, storing separately the documents and their use in scenarios, or in the case of executable code in autonomous segments. Next, in order to promote the gradual exploration, understanding, evaluation and choice of learning objects, it is important to link the resources not only with metadata, but also explicit documentation on the theoretical and practical aspects of their use, as well as any relevant evaluation material. Finally, if we really want these resource banks to hold this rich ancillary information, we need to build tools that support this contextualization and the activities of all the actors in the telelearning environment from conception, through development and use.